Do partner services linked to molecular clusters yield people with viremia or new HIV?. (1st May 2022) - Schneider, John A.; Hayford, Christina; Hotton, Anna; Tabidze, Irina; Wertheim, Joel O.; Ramani, Santhoshini; Hallmark, Camden; Morgan, Ethan; Janulis, Patrick; Khanna, Aditya; Ozik, Jonathan; Fujimoto, Kayo; et al.
Abstract : Objectives: We examined whether molecular cluster membership was associated with public health identification of HIV transmission potential among named partners in Chicago. Design: Historical cohort study. Methods: We matched and analyzed HIV surveillance and partner services data from HIV diagnoses (2012–2016) prior to implementation of cluster detection and response interventions. We constructed molecular clusters using HIV-TRACE at a pairwise genetic distance threshold of 0.5% and identified clusters exhibiting recent and rapid growth according to the Centers for Disease Control and Prevention definition (three new cases diagnosed in past year). Factors associated with identification of partners with HIV transmission potential were examined using multivariable Poisson regression. Results: There were 5208 newly diagnosed index clients over this time period. Average age of index clients in clusters was 28; 47% were Black, 29% Latinx/Hispanic, 6% female and 89% MSM. Of the 537 named partners, 191 (35.6%) were linked to index cases in a cluster and of those 16% were either new diagnoses or viremic. There was no statistically significant difference in the probability of identifying partners with HIV transmission potential among index clients in a rapidly growing cluster versus those not in a cluster [adjusted relative risk 1.82, (0.81–4.06)]. Conclusion: Partner services that were initiated from index clients in a molecular cluster yielded similar new HIV case finding or identification of those with viremia as did interviews with index clients not in clusters. It remains unclear whether these findings are due to temporal disconnects between diagnoses and cluster identification, unobserved cluster members, or challenges with partner services implementation.